2022
DOI: 10.1038/s41467-022-32114-5
|View full text |Cite
|
Sign up to set email alerts
|

Flexible-type ultrathin holographic endoscope for microscopic imaging of unstained biological tissues

Abstract: Ultrathin lensless fibre endoscopes offer minimally invasive investigation, but they mostly operate as a rigid type due to the need for prior calibration of a fibre probe. Furthermore, most implementations work in fluorescence mode rather than label-free imaging mode, making them unsuitable for general medical diagnosis. Herein, we report a fully flexible ultrathin fibre endoscope taking 3D holographic images of unstained tissues with 0.85-μm spatial resolution. Using a bare fibre bundle as thin as 200-μm diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…, where ΔD eff is the average core-to-core spacing of the fiber bundle. 31 In applications where endoscopic imaging is conducted for targets with low reflectance, such as biological tissues, it often becomes necessary to position the fiber probe close to the sample to capture more signals. In such scenarios, the reduction of the view field diameter of the previous algorithms, which is proportional to the distance, becomes a major problem.…”
Section: Comparison Between Different Lossmentioning
confidence: 99%
“…, where ΔD eff is the average core-to-core spacing of the fiber bundle. 31 In applications where endoscopic imaging is conducted for targets with low reflectance, such as biological tissues, it often becomes necessary to position the fiber probe close to the sample to capture more signals. In such scenarios, the reduction of the view field diameter of the previous algorithms, which is proportional to the distance, becomes a major problem.…”
Section: Comparison Between Different Lossmentioning
confidence: 99%
“…Alternatively, a transmission matrix can be calibrated by illuminating the proximal end and measuring the backward propagating wavefronts from the partial reflectors at the distal tip 78 80 Recently, it has also been shown that a target object itself can serve as a guide star to identify the core-to-core phase retardations of the MCF and reconstruct a diffraction-limited and pixelation-free image 81 . With the reflection matrix of the MCF measured with core-to-core illumination, the singly-reflected waves from a target object can be coherently accumulated based on the adaptive algorithm, called closed-loop accumulation of single scattering 82 …”
Section: Advanced Techniquesmentioning
confidence: 99%
“…[78][79][80] Recently, it has also been shown that a target object itself can serve as a guide star to identify the core-to-core phase retardations of the MCF and reconstruct a diffractionlimited and pixelation-free image. 81 With the reflection matrix of the MCF measured with core-to-core illumination, the singly-reflected waves from a target object can be coherently accumulated based on the adaptive algorithm, called closed-loop accumulation of single scattering. 82 Another notable approach is to estimate the transmission matrix from the partial information of the matrix elements, which is possible due to the cylindrically symmetric behavior of light within conventional optical fibers with a circular cross-section, called the "rotational memory effect."…”
Section: In Situ Transmission Matrix Calibrationmentioning
confidence: 99%
“…Combined with computational imaging methods, MCF imaging technology can achieve a high imaging resolution and flexibility . [14][15][16] Choi et al reported a fully flexible ultrathin fiber endoscope obtaining 3D holographic images of unstained tissues . [15] Orth et al proved that MCF can record depth information and realize 3D imaging .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Choi et al reported a fully flexible ultrathin fiber endoscope obtaining 3D holographic images of unstained tissues . [15] Orth et al proved that MCF can record depth information and realize 3D imaging . [17] However, MCFbased endoscopes have limitations such as low resolution, large footprint, and pixelated images.…”
Section: Introductionmentioning
confidence: 99%